Differentially methylated loci in NAFLD cirrhosis are associated with key signaling pathways - Gerhard, Glenn S. (Clin Epigenetics, 2018)
Altered DNA methylation events contribute to the pathogenesis and progression of metabolic disorders, including nonalcoholic fatty liver disease (NAFLD). Investigations of global DNA methylation patterns in liver biopsies representing severe NAFLD fibrosis have been limited. We used the HumanMethylation 450K BeadChip to analyze genome-wide methylation in patients with biopsy-proven grade 3/4 NAFLD fibrosis/cirrhosis (N = 14) and age- and sex-matched controls with normal histology (N = 15). We identified 208 CpG islands (CGIs), including 99 hypomethylated and 109 hypermethylated CGIs, showing statistically significant evidence (adjusted P value < 0.05) for differential methylation between cirrhotic and normal samples. Comparison of β values for each CGI to the read count of its corresponding gene obtained from RNA-sequencing analysis revealed negative correlation (adjusted P value < 0.05) for 34 transcripts. These findings provide supporting evidence for a role for CpG methylation in the pathogenesis of NAFLD-related cirrhosis, including confirmation of previously reported differentially methylated CGIs, and contribute new insight into the molecular mechanisms underlying the initiation and progression of liver fibrosis and cirrhosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-018-0525-9) contains supplementary material, which is available to authorized users.